Analisis terhadap Keabsahan Surat Kuasa WNI dari Luar Negeri Untuk Beracara di Pengadilan Indonesia - William S; Gunawan Podiman (Jurnal Suara Hukum, 2021)
There will be the time when people need other for represent things, which is use a power of attorney. A power of attorney is a valid statement from one to another to do things. It discuss about Indonesian citizens from abroad to be valid appear in the Indonesian Court. It also discuss the validality power of attorney documents of Indonesian citizens from Indonesia to appear in foreign courts. Uses secondary data from journals, articles, books and internet sites as references. The terms of a power of attorney made abroad is to submit and participate in the provisions of the court where the lawsuit can be received or filed or known by the basic name lex fori. In addition, overseas power of attorney can also be considered valid if legalized by the local Embassy, the Ministry of Foreign Affairs, and the Ministry of Law and Human Rights. Legalization is done as a legal assurance for the court in Indonesia that it is true that the creation of a power of attorney in the country concerned so as not to raise doubts. We need to concern about the four absolute requirements contained in SEMA No. 2 of 1959. If one of the conditions not fulfilled, then the power of attorney is considered invalid.